Moral Values Of Main Character In Bumblebee Movie Directed By Travis Knight - Yanti Rosalinah; Syifa Aulia; Ibnu Subroto (Wanastra: Jurnal Bahasa dan Sastra, 2021)
Nowadays, watching a movie has become a daily activity for some people, even become a hobby. Sometimes humans just watch and forget some important things we can take from the movie. One of them is a moral value that we can set as an example to deal with various problems of life. That is the purpose of this paper. The writer wants to convey the moral values that can be taken from the film to the readers or viewers of the movie. In analyzing this paper, The writer uses descriptive qualitative method and the techniques by descriptive observation (collecting). So here, The Writer will examine the bumblebee film with data in the form of words and images from the film. Then the procedure for collecting data using observation techniques (field notes). Collecting technique the data needed and the theory is through internet research. The result of this research is first, types of moral values in Bumblebee that appear in the movie and the second is which types of moral value most appear in the movie. There are eight types of moral values in this movie. They are patriotism, work hard, friendly or communicative, creative, care to social, curious, independent, and appreciate achievement